Digital-forensics and watermarking : 14th International Workshop, IWDW 2015, Tokyo, Japan, October 7-10, 2015 : revised selected papers /: 14th International Workshop, IWDW 2015, Tokyo, Japan, October 7-10, 2015 : revised selected papers. (2016) - Unknown
No abstract available